The European Customer Satisfaction Index (ECSI) Model: Development of, and Testing the Validity, Reliability, and Independence of the Constructs in, an Instrument for Explaining Student Satisfaction in the Context of Universities in Uganda - Kyoshaba, Martha; Bakkabulindi, Fred E.K. (Journal of African Interdisciplinary Studies, 2023)
The European Customer Satisfaction Index (ECSI) model suggests that the satisfaction of students as customers of universities is predicted by University Image (UI), Student Expectations (SE), Service Quality of Infrastructure and Tangible Service Elements (SQITSE), Service Quality of People and Processes (SQPP) and Perceived Value of Investment (PVI). In turn, PVI is predicted by UI, SE, SQITSE and SQPP. Furthermore, Student Loyalty (SL) is predicted by Student Satisfaction (SS), UI and SQPP; and finally, SE is predicted by UI. In this paper we developed an instrument on the explanatory constructs of the ECSI model. After which we sought to answer two questions: (i) to what extent was each of the explanatory constructs in the instrument on the ECSI model valid and reliable and (ii) were the explanatory constructs in our instrument on the ECSI model independent? A sample of 704 students from seven universities in Uganda responded to our self-administered questionnaire (SAQ). For analysis, we applied the (i) confirmatory factor analysis (CFA) and Cronbach alpha (α); and (ii) Pearson’s linear correlation (PLC) for our two respective questions. Using CFA, we established that: (i) All the items of each of the five constructs (UI, SE, SQPP, PVI, and SL) in our instrument were valid but the construct SQITSE was only valid after we dropped some of its items. The alpha results showed that all the constructs in our instrument were reliable. (ii) However, our PLC results suggested that the explanatory constructs were significantly interrelated. Hence, we recommend that studies use our instrument with the view of refining it.
Keywords: Cronbach Alpha; ECSI; Factor Analysis; Instrument; Reliability; Satisfaction; Student; Validity; Uganda; Universities